Semi-continuous culture of a microalgal consortium in open ponds under greenhouse conditions using piggery wastewater effluent. (December 2020) - Fernández-Linares, Luis C.; Gutiérrez-Márquez, Alejandra; Guerrero-Barajas, Claudia
Abstract: Semi-continuous microalgal consortium cultivation was completed in 200 L open raceway ponds under greenhouse conditions using piggery as substrate (added at an appropriate concentration to reach 80 mg of NH4 + /L) as culture medium. A number of 6 cycles of 13 days each were completed, between February and April. The biomass, lipids, carbohydrates, proteins and pigments productions, the removal of ammonia, orthophosphates, and COD, as well as the variation of the nitrogen species in the medium were evaluated. The maximum production of cellular biomass, proteins, lipids, and carbohydrates was of 4.98 × 10 6 cell/mL, 610.28, 189.78 and 157.80 mg/L, respectively. The fatty acid composition consisted mainly of palmitic acid (C16: 0), palmitoleic acid (C18:1), and linolenic acid (C18:3). Unsaturated fatty acids were the largest fraction in a range of 36.85 to 37.72% and monounsaturated from 23.61 to 31.80%. The removal of ammonia, orthophosphates, and COD was 100, 81.40, and 90.64%, respectively. Graphical abstract: Unlabelled Image Highlights: Semi-continuous culture of a microalgae consortium in pig wastewater was evaluated. Nutrients were rapidly removed by consortium, particularly in synergy with bacteria. The microalgal biomass obtained presents a high protein and lipid content. The main lipidic fraction (biomass) was of unsaturated/monounsaturated fatty acids.